2013
DOI: 10.1001/jama.2013.193
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia

Abstract: Key Clinical Question-How does one diagnose and treat insomnia in adults?Evidence Review-Summary of meta-analyses of chronic insomnia treatments.Bottom Line-Insomnia is a common clinical condition characterized by difficulty initiating or maintaining sleep, accompanied by symptoms such as irritability or fatigue during wakefulness. The prevalence of insomnia disorder is approximately 10-20%, with approximately 50% having a chronic course. Insomnia is a risk factor for impaired function, the development of othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
584
1
18

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 811 publications
(610 citation statements)
references
References 53 publications
(75 reference statements)
7
584
1
18
Order By: Relevance
“…131 As reviewed by Buysse 132 and Morin and Benca, 7 the effi cacy of Cognitive Behavioral Th erapy for Insomnia for the treatment of insomnia has been demonstrated. Although these approaches make eff orts toward reducing cognitive and emotional arousal, there has also been a call for therapies that target physiologic hyperarousal across the night and day.…”
Section: Unit Of Analysis Evidence For This Perspective In Pathophysimentioning
confidence: 99%
“…131 As reviewed by Buysse 132 and Morin and Benca, 7 the effi cacy of Cognitive Behavioral Th erapy for Insomnia for the treatment of insomnia has been demonstrated. Although these approaches make eff orts toward reducing cognitive and emotional arousal, there has also been a call for therapies that target physiologic hyperarousal across the night and day.…”
Section: Unit Of Analysis Evidence For This Perspective In Pathophysimentioning
confidence: 99%
“…In the present study MTrP injection into the gastrocnemius muscle was effective in relieving the pain of NCCs, corresponding with the results of a study by Prateepavanich et al 14 Insomnia is a clinical condition characterized by difficulty initiating or maintaining sleep, accompanied by symptoms such as irritability or fatigue during wakefulness. 26 In general, painful conditions and sleep disturbance may influence each other, 27,28 and nocturnal episodes of pain in particular are reported to change sleep architecture, induce phases of arousal, and even trigger awakening. 29 Hawke et al 2 showed that NCCs had a substantial connection with reduced quality of sleep and, by extension, affected health-related quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…1 The high prevalence of chronic insomnia among patients with chronic pain has been well-established, with reported rates of insomnia as high as 88% in this population. 2,3 Independently, sleep and pain are known to be associated with a host of negative consequences including decreased quality of life, mood disturbance, impaired quality of social interactions, dependence on medication, and cognitive dysfunction.…”
Section: Introductionmentioning
confidence: 99%